Shock Wave Therapy Improves Cardiac Function in a Model of Chronic Ischemic Heart Failure: Evidence for a Mechanism Involving VEGF Signaling and the Extracellular Matrix. Issue 20 (16th October 2018) - Gollmann‐Tepeköylü, Can; Lobenwein, Daniela; Theurl, Markus; Primessnig, Uwe; Lener, Daniela; Kirchmair, Elke; Mathes, Wolfgang; Graber, Michael; Pölzl, Leo; An, Angela; Koziel, Katarzyna; Pechriggl, Elisabeth; et al.
Abstract : Background: Mechanical stimulation of acute ischemic myocardium by shock wave therapy (SWT) is known to improve cardiac function by induction of angiogenesis. However, SWT in chronic heart failure is poorly understood. We aimed to study whether mechanical stimulation upon SWT improves heart function in chronic ischemic heart failure by induction of angiogenesis and postnatal vasculogenesis and to dissect underlying mechanisms. Methods and Results: SWT was applied in a mouse model of chronic myocardial ischemia. To study effects of SWT on postnatal vasculogenesis, wild‐type mice received bone marrow transplantation from green fluorescence protein donor mice. Underlying mechanisms were elucidated in vitro in endothelial cells and murine aortic rings. Echocardiography and pressure/volume measurements revealed improved left ventricular ejection fraction, myocardial contractility, and diastolic function and decreased myocardial fibrosis after treatment. Concomitantly, numbers of capillaries and arterioles were increased. SWT resulted in enhanced expression of the chemoattractant stromal cell–derived factor 1 in ischemic myocardium and serum. Treatment induced recruitment of bone marrow–derived endothelial cells to the site of injury. In vitro, SWT resulted in endothelial cell proliferation, enhanced survival, and capillary sprouting. The effects were vascular endothelial growth factor receptor 2 and heparan sulfate proteoglycan dependent. Conclusions: SWT positively affects heart function in chronic ischemic heart failure by induction of angiogenesis and postnatal vasculogenesis. SWT upregulated pivotal angiogenic and vasculogenic factors in the myocardium in vivo and induced proliferative and anti‐apoptotic effects on endothelial cells in vitro. Mechanistically, these effects depend on vascular endothelial growth factor signaling and heparan sulfate proteoglycans. SWT is a promising treatment option for regeneration of ischemic myocardium.